Search Engine for Halal Linked Open Data Using Entity Ranking Approach - Ahmad Choirun Najib; Nur Aini Rakhmawati (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Halal concept is an essential aspect of Muslim daily life. Currently, many organizations around the world provide halal certification services as known as halal certification bodies. In the majority, these organizations provide halal product information on their website. However, information is presented in different formats, such as pdf, table, and text. As a result, the user is difficult to search for information on these websites. Therefore, we develop search engine on halal linked open data to facilitate users for searching halal products. We use an entity ranking approach to retrieve relevant items based on user queries that consist of an independent-ranking and dependent-ranking method. Independent ranking employs a link-count approach to indicate the information richness of the entity. Dependent ranking employs term frequency-inverse entity frequency  (TF-IEF) to measure the similarity of an entity based on terms. We use Apache Lucene to perform indexing and search process. Also, we use the Neo4j graph database to save entity ranking computation results. The results show that the system delivers excellent results. The Mean Average Precision (MAP) for top-5 results is 91,2%.